Surface energy increase of oxygen-plasma-treated PET - Cioffi, MOH; Voorwald, HJC; Mota, Rogério Pinto [UNESP] (Elsevier B.V., 2003)
Prosthetic composite is a widely used biomaterial that satisfies the criteria for application as an organic implant without adverse reactions. Polyethylene therephthalate (PET) fiber-reinforced composites have been used because of the excellent cell adhesion, biodegradability and biocompatibility. The chemical inertness and low surface energy of PET in general are associated with inadequate bonds for polymer reinforcements. It is recognized that the high strength of composites, which results from the interaction between the constituents, is directly related to the interfacial condition or to the interphase. A radio frequency plasma reactor using oxygen was used to treat PET fibers for 5, 20, 30 and 100 s. The treatment conditions were 13.56 MHz, 50 W, 40 Pa and 3.33 x 10(-7) m(3)/s. A Rame-Hart goniometer was used to measure the contact angle and surface energy variation of fibers treated for different times. The experimental results showed contact angle values from 47degrees to 13degrees and surface energies from 6.4 x 10(-6) to 8.3 x 10(-6) J for the range of 5 to 100 s, respectively. These results were confirmed by the average ultimate tensile strength of the PET fiber/polymethylmethacrylate (PMMA) matrix composite tested in tensile mode and by scanning electron microscopy. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: plasma treatment; PET/PMMA; composite; contact angle; tensile strength